2016
DOI: 10.1016/j.cnp.2016.03.002
|View full text |Cite
|
Sign up to set email alerts
|

Psychophysical estimate of plantar vibration sensitivity brings additional information to the detection threshold in young and elderly subjects

Abstract: HighlightsPsychophysical estimate of plantar vibration perception (n coefficient) was obtained.In all subjects higher n values were measured at the 150 Hz vibration frequency.n values bring complementary information of vibration detection threshold.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(14 citation statements)
references
References 21 publications
(40 reference statements)
0
14
0
Order By: Relevance
“…As in our previous study [13], we found that the sole determination of the vibration threshold gave less information than the Stevens power function did. Indeed, an increased skin hardness was only associated to an elevated vibration threshold at the 25 Hz vibration frequency while the k coefficient of the Stevens power function was affected at both the 25 and 150 Hz frequencies.…”
Section: Discussionmentioning
confidence: 44%
See 3 more Smart Citations
“…As in our previous study [13], we found that the sole determination of the vibration threshold gave less information than the Stevens power function did. Indeed, an increased skin hardness was only associated to an elevated vibration threshold at the 25 Hz vibration frequency while the k coefficient of the Stevens power function was affected at both the 25 and 150 Hz frequencies.…”
Section: Discussionmentioning
confidence: 44%
“…This could explain the absence of any significant correlation between the perceptual vibration threshold and the skin hardness. Second, the authors only measured the vibration threshold and the present study, as our previous one [13], clearly showed a poor discriminating power of the sensitivity threshold.…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…The activation of the cutaneous afferents gives perceptual information that reveals relationships between the estimate of the vibratory stimuli and their physical magnitude. This was confirmed for the mechanosensitivity of the hand [ 18 ] and the foot sole [ 15 , 19 , 20 ].…”
Section: Introductionmentioning
confidence: 72%